Endometrial tissue sampling using pipelle versus dilatation and curettage for the assessment of endometrium in patients of perimenopausal and post-menopausal age: a prospective study - Navakumar, Nina; Dinesh, Dhanya; Devi, P. K. Syamala (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The aim of this study is to compare the accuracy and adequacy of endometrial sampling using pipelle biopsy with dilatation and uterine curettage (D and C) and hysterectomy specimen in the assessment of endometrium in patients of perimenopausal and postmenopausal age. Methods: One hundred fifty patients of perimenopausal and postmenopausal age who attended the Gynecology OPD of KIMS Hospital from June 2012 to May 2014 with complaints of abnormal uterine bleeding or who were found to have abnormally thickened endometrium by ultrasonography were included in the study. Results: Adequate specimen could be obtained through pipelle biopsy in 86.7% of the patients, compared to 76% with adequate sample in case of D and C. Comparing histopathology reports between Pipelle and DandC specimens, the confidence interval was 92.7%, 95% lying in the range between 86.54% to 96.53%. 68 of the 150 patients had undergone hysterectomy for various reasons. Comparing histopathology reports between Pipelle and hysterectomy specimens, the confidence interval was 94.2%; 95% of study population lies within the C.I range of 84.05 %-98.79% while accounting for the whole population, which shows that Pipelle endometrial sampling can be considered to be almost accurate as HPE by hysterectomy specimen. Comparing the difficulty of the procedure, Pipelle biopsy was found to be easier in perimenopausal patients when compared to post-menopausal patients and the difference was statistically significant. Mode of delivery did not seem to affect the ease of Pipelle endometrial sampling as per present observations. Conclusions: Endometrial tissue sampling using Pipelle was found to be as reliable as D and C and hysterectomy specimen on histopathologic examination for the assessment of endometrium in perimenopausal and post-menopausal age group. Pipelle endometrial sampling was found to be yield adequate specimen when compared with D and C.